2017
DOI: 10.1038/srep40155
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1-ErbB module in C-bouton synapses on somatic motor neurons: molecular compartmentation and response to peripheral nerve injury

Abstract: The electric activity of lower motor neurons (MNs) appears to play a role in determining cell-vulnerability in MN diseases. MN excitability is modulated by cholinergic inputs through C-type synaptic boutons, which display an endoplasmic reticulum-related subsurface cistern (SSC) adjacent to the postsynaptic membrane. Besides cholinergic molecules, a constellation of proteins involved in different signal-transduction pathways are clustered at C-type synaptic sites (M2 muscarinic receptors, Kv2.1 potassium chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 73 publications
5
40
0
Order By: Relevance
“…We next asked if axonal injury-induced changes in MNs and their synaptic and glial environment (42) also affect SSC-associated NRG1 clusters. We recently showed that microglial processes are rapidly attracted to C-boutons of axotomized MNs (11). Here, we extended these findings by performing a long-term analysis in both reversible (crush) and irreversible (axotomy) axonal interruption paradigms ( Fig.…”
Section: Glial Reactivity and C-bouton Plasticity After Reversible Anmentioning
confidence: 52%
See 4 more Smart Citations
“…We next asked if axonal injury-induced changes in MNs and their synaptic and glial environment (42) also affect SSC-associated NRG1 clusters. We recently showed that microglial processes are rapidly attracted to C-boutons of axotomized MNs (11). Here, we extended these findings by performing a long-term analysis in both reversible (crush) and irreversible (axotomy) axonal interruption paradigms ( Fig.…”
Section: Glial Reactivity and C-bouton Plasticity After Reversible Anmentioning
confidence: 52%
“…Nevertheless, a more detailed examination revealed that although S1R and NRG1 were closely associated, they did not occupy identical microdomains (Fig. 7C, D), very similar to their configuration in C-boutons from WT mice (11). In contrast, a close apposition between NRG1 and Kv2.1 was observed (Pearson's r .…”
Section: Distinct Nrg1 Isoforms Mediate Specific Pre-and Postsynapticmentioning
confidence: 87%
See 3 more Smart Citations